Review: Auditory Integration Training - Zahra Ja'fari (University of Social Welfare and Rehabilitation Sciences, 2003)
Auditory integration training (AIT) is a hearing enhancement training process for sensory input anomalies found in individuals with autism, attention deficit hyperactive disorder, dyslexia, hyperactivity, learning disability, language impairments, pervasive developmental disorder, central auditory processing disorder, attention deficit disorder, depression, and hyper acute hearing. AIT, recently introduced in the United States, and has received much notice of late following the release of the sound of a miracle, by Annabel Stehli. In her book, Mrs. Stehli describes before and after auditory integration training experiences with her daughter, who was diagnosed at age four as having autism.